Must the Social be Reassembled? Broken Dispute between B. Latour and P. Bourdieu - Poviliūnas, Arūnas (Sociologija. Mintis ir veiksmas, 2020)
The article analyses the conflict between two prominent French sociologists P. Bourdieu and B. Latour. It attempts to answer a question to what extent this conflict reflects the paradigmatic break of sociology. The study of the conflict concludes with the statement that the attempts of B. Latour and his allies to “reassemble the social” and institutionalize Actor-Network-Theory resulted in the critical movement of the Science Technology Studies (STS). However, STS does not succeed to become the paradigmatic break of the path of sociology.